European and Italian regulation on orphan medicinal products - Joppi, Roberta (Farmeconomia. Health Economics and Therapeutic Pathways, 2013)
The paper presents an overview of the European and Italian Regulation on Orphan Medicinal Products (OMPs), along with some data on the OMPs licensed in the EU from 2000 to 2012. The EU legislation encourages pharmaceutical companies to develop drugs for rare diseases, so-called “orphan drugs”. The European Medicine Agency recognizes orphan drug status mainly on the basis of the prevalence of the disease (≤ 5/10,000), and potential benefit. Orphan status implies incentives for pharmaceutical companies. From 2000 up to 2012 890 candidate orphan drug designations received a positive opinion and the marketing authorization was granted to 72 OMPs corresponding to 80 different indications. Currently, 59 OMPs are available to Italian patients either because licensed to the market by the AIFA or included in the list of the L. 648/96. Despite of an encouraging regulation nearly all the currently estimated rare diseases still await treatments.